PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III-A SD NEGERI 73BALAI MAKAM KECAMATAN MANDAU KABUPATEN BENGKALIS - Nurlaina, Nurlaina; Hamizi, Hamizi; Erlisnawati, Erlisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Some of the finding problems in the learning process of science at third grade students of SD Negeri 73 Balai Makam were: some of them were not serious in the learning process. This caused that most students got low score of science examination. 11 students (40%) were able to get 70 as the minimal score of science, but 26 students (60%) only got score below 70. As this result motivated the researcher to conduct the action research to increase the students’ ability in science. This research has been conducted from March to April 2015. The action conducted into two cycles. Each cycle consisted of two meetings. The subject of this research was the third grade students of SD Negeri 73 Balai Makam, Kecamatan Mandau Kabupaten Bengkalis. There were 27 students, 13 boys dan 14 girls. The score of the teacher’s activity at cycle 1 first meeting was 56 category less increased in second meeting to be 62.5 category less. It increased to be 65.2 at the cycle 2 first meeting, and being 75 category enough at second meeting. AT the first cycle, it was found that only some active students, but at the secondcycle, most students were more active and giving their participation in learning process. The success of this action research can be seen from the students’ result in examination from 63.3 category less to be 72.2 category enoughin the second cycle. The increasing of the stduents’ score at second cycle was 14.0%.Key words : Learning model, inquiry, the result of science